Descriptive Epidemiology of Interruptions to Free-Living Sitting Time in Middle-Age and Older Adults. Issue 12 (December 2021) - BLANKENSHIP, JENNIFER M.; WINKLER, ELISABETH A. H.; HEALY, GENEVIEVE N.; Dempsey, PADDY C.; BELLETTIERE, JOHN; OWEN, NEVILLE; DUNSTAN, DAVID W.
ABSTRACT: National guidelines recommend physically active interruptions to sitting time; however, the characteristics of these interruptions are broadly stated and ill-defined. A robust methodology for population surveillance for such interruptions is needed. Purpose: To describe the frequency and characteristics (i.e., duration, stepping time, and estimated intensity) of all interruptions and physically active interruptions to adults' free-living sitting time (i.e., transitions from sitting to upright posture) across segments of the population. Methods: Australian Diabetes, Obesity and Lifestyle study participants (321 men; 406 women; mean ± standard deviation, 58.0 ± 10.3 yr) wore the activPAL3™ for ≥1 valid day. The characteristics of interruptions from laboratory studies demonstrating health benefits were selected to define active interruptions (≥5 min upright and/or ≥2 min stepping) and ambulatory interruptions (≥2 min stepping). The frequency and characteristics of all, active, and ambulatory interruptions were described and compared by age, sex, diabetes status, and body mass index. Results: Adults averaged 55.0 ± 21.8 interruptions per day, but only 20.3 ± 6.7 were active and 14.0 ± 5.4 were ambulatory. Median (25th, 75th percentile) duration was 2.6 min (0.9, 7.8 min), stepping time was 0.8 min (0.3, 2.0 min), and estimated energy expenditure was 4.3 metabolic equivalents (MET)·min −1 (1.4, 12.5 MET·min −1 ). Those who were older, had obesity, or had diabetes had significantly ( P < 0.05) fewer interruptions of all types and less stepping time during active interruptions than their counterparts (Cohen's d < 0.2). Conclusions: Free-living interruptions were often less active than interruptions performed in effective acute laboratory studies and their content varied widely between population groups. Monitoring all interruptions, as well as those that are more active, is advisable to provide a comprehensive understanding of free-living sedentary behavior. Abstract : Supplemental digital content is available in the text.